2016
DOI: 10.3348/kjr.2016.17.5.734
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Infiltrative Splenic Lymphoma: Diagnostic Efficacy of Arterial-Phase CT

Abstract: ObjectiveTo evaluate the diagnostic performance of obliteration of normal heterogeneous enhancement of the spleen (ONHES) on arterial phase (AP) computed tomography (CT) images in diffuse infiltrative splenic lymphoma (DISL).Materials and MethodsOne hundred and thirty-six patients with lymphoma who had undergone two-phase (arterial and portal venous) abdominal CT were included in this study. We retrospectively evaluated the diagnostic performance of ONHES on AP CT in diagnosing DISL. Two observers evaluated ON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In humans, it has been suggested that infiltrative splenic lymphoma typically affects the periarterial lymphatic sheaths (PALS) of the white pulp. As a result, it is believed that the white pulp’s involvement, which reduces its flow rate, is primarily responsible for the obliteration of splenic heterogeneity ( 21 ). Therefore, it is likely that a similar mechanism suggested in humans led to the observation of these findings in cats with DISL; however, more comprehensive research including histological evaluations is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, it has been suggested that infiltrative splenic lymphoma typically affects the periarterial lymphatic sheaths (PALS) of the white pulp. As a result, it is believed that the white pulp’s involvement, which reduces its flow rate, is primarily responsible for the obliteration of splenic heterogeneity ( 21 ). Therefore, it is likely that a similar mechanism suggested in humans led to the observation of these findings in cats with DISL; however, more comprehensive research including histological evaluations is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the absence of splenomegaly is not sufficient to exclude a diagnosis of infiltrative tumors, which can manifest as a normally appearing spleen with microscopic involvement only ( 18 , 20 ). In humans, it is reported that in conjunction with subjective splenomegaly, the obliteration of normal heterogeneous enhancement patterns of the spleen on CT can improve the diagnostic performance for diffuse infiltrative splenic lymphoma ( 21 ). However, to the best of our knowledge, there is no study related to these changes of splenic enhancement on CT in cats with diffuse infiltrative splenic lesions (DISL).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the DTA studies, one reviewer experienced in DTA studies selected eligible articles according to criteria established elsewhere ( 9 ) with additional confirmation by another DTA expert in cases of ambiguity. Of the initial 124 candidate articles, 63 articles ( 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 ) were finally included. Regarding the studies that analyzed reliability, eligible articles were chosen by consensus after review by two of four independent reviewers experienced in the relevant methodology.…”
Section: Methodsmentioning
confidence: 99%
“…These studies could be viewed as extensions of DTA analysis of non-binary data, which require different statistical analyses ( 81 ), than the standard analysis used for reliability, although some published studies seem to have failed to distinguish between them. Of the initial 71 article candidates, 36 articles ( 15 19 42 45 53 57 58 64 66 67 69 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 ) were finally included.…”
Section: Methodsmentioning
confidence: 99%
“…Among the many possible causes of splenomegaly, lymphoma is the most vital to detect because the additional information gleaned from such detection can aid in establishing the proper tumor staging, treatment protocols, and prognosis [4]. Pathological confirmation of the lesion can be performed through percutaneous biopsy of the spleen.…”
Section: Introductionmentioning
confidence: 99%